Dova, Evanthia - (:unkn) unknown (My University, 2026)
Born in Thessaloniki, Greece (1974). Studied in the School of Architecture, Faculty of Engineering, Aristotle University of Thessaloniki (AUTh) (Diploma in Architecture, 1998) and the Yale University School of Architecture (ΜArch II, 2000). Completed her PhD dissertation, titled “Imaginary considerations of dwelling through the spatial and social structure of the Greek urban development: the case of Panorama, Thessaloniki”, under the supervision of Prof. V. Tentokali, in the AUTh School of Architecture. She has been professionally involved in private and public projects, and architecture competitions, in architecture studios in New York City and Thessaloniki. She has also served as a Scientific Associate for the European Center for Byzantine and Post-Byzantine Monuments in Thessaloniki (2005-2008). She has taught architectural design in the AUTh School of Architecture and the School of Architectural Engineering, Technical University of Crete as an Adjunct Lecturer, and in Yale University, as a Teaching Fellow. Since 2010, she is a Lecturer in Architecture at the School of Architecture, Engineering, Land and Environmental Sciences, Neapolis University Pafos, Cyprus, teaching in the Undergraduate Program in Architecture and the Postgraduate Program in Landscape Architecture. She has supervised research and diploma theses, has curated exhibitions, participated in workshops and is a consultant on urban spaces for the Municipality of Pafos. She has co-edited the book “[Architectonikes Theseis] – Architecture Theses │ 1” (2022), the proceedings of the international conference “Transparency and Architecture: limits and challenges” (2006), and the publication “Byzantine Monuments in the Society of Information” (2006). Her research focuses on the one hand on issues of dwelling in the center and the periphery of the city, and interdisciplinary understandings of home, and on the other hand on urban public spaces, with a specific interest in the interactions among cultural heritage, mega-events and urban development.